Organismos emergentes : prácticas éticas de pesca y crisis moral en Bahía Solano, Chocó (2017)
In this work, I analyze the way in which the use of certain fishing technologies (re)create the world of the fishermen involved with the community company "Red de Frío", main provider of fish for the restaurant Wok, located in Bogotá, Colombia. Along the text, I go back to the proposal of Ingold (2000) to develop and analysis of the "environmental and social situated practices" by thinking about the use of the fishing gear in terms of skills. Since the study of the skill assumes an ecological approach, I sought to identify the dynamic and adaptive relationships that the fishermen stablish with their environment while exploring the moral and ethical forms of being-in-the-word (Zigon, 2007) that get configurated from the appropriation, alteration and diffusion of certain artefacts and practices associated with fishing.